Correlation between test anxiety and students’ chemistry achievement - Nwafor, Stephen Chinedu; Eke, Joy Anulika; Ibe, Franklin Nnanna (Univeritas Papua, 2023)
This research examined the correlation between test anxiety and chemistry students’ achievement. It also looked at the moderating effect of school location and gender on the correlation between these two variables. In the study, a descriptive survey design was used. Using stratified random sampling, 222 chemistry students from senior secondary schools were selected. The instruments used were test anxiety questionnaire and chemistry achievement test. Pearson correlation and coefficient of determination were used for data analysis. The study indicated a significant negative correlation between test anxiety and chemistry achievement among students. In addition, there was no correlation between test anxiety and students' performance in chemistry when school location and gender were moderated for. It was therefore concluded that an increase in students’ test anxiety will decrease their achievement in chemistry and vice-versa, irrespective of their school location and gender. Consequently, it was recommended, among others, that the teachers, parents, curriculum planners and education stakeholders use cognitive, affective and behavioural approaches to minimize students' test anxiety to increase their achievement.